Dielectric Metasurfaces: Free‐Electron Transparent Metasurfaces with Controllable Losses for Broadband Light Manipulation with Nanometer Resolution (Advanced Optical Materials 1/2020). Issue 1 (3rd January 2020) - Bonifazi, Marcella; Mazzone, Valerio; Li, Ning; Tian, Yi; Fratalocchi, Andrea
Abstract : In article number 1900849, Andrea Fratalocchi and co‐workers present the nanofabrication of a liquid metasurface for the manufacturing of optical circuitry with ultra‐dense resolution. The process exploits a flux of free‐electrons possessing high fluency to modify the quantum resonances of single atoms composing the material, printing a desired distribution of refractive index and absorption losses with the focusing accuracy of the electron beam, theoretically limited to the single nanometer.